Analysis of the behavior of means of payment other than cash, atms and virtual banking, 2013 – 2021 - Arámbulo Ayala de Sánchez, Marizol Candelaria (2022)
Nowadays, some means of payment have been transformed to digital means, granting a variety of options that offer a better user experience. In this sense, the goal of the present research was analyze the trend of the use of payment methods other than cash, ATMs and virtual banking, 2013 - 2021, with a quantitative approach, basic type, descriptive level, non-experimental design and longitudinal court, using information from the Banco Central de Reserva del Perú. The results determined that there is a growing and significant trend in the use of virtual banking and that with the arrival of Covid-19, personal and business transactions were adapted to the use of technology. In the same way, transfers and debit cards have had a growing behavior, the use of ATMs has had a minimal growth and the use of checks, as a means of payment different to cash, has had a decreasing trend.